Effect of Subsequent Aging in SiC P Reinforced AA2124 Aluminum Metal Matrix Composite - ARTIR, RECEP; SALMAN, SERDAR; BOZKURT, YAHYA (My University, 2009)
The present study is focused on the evaluation of the aging behaviour and microstructure characterization of AA2124/SiC/25p composite under the aging temperatures of 180, 185 and 190 °C for various dwelling time ranging from 0 up to 100 hours. The microstructure was characterized by means of scanning electron microscopy. The hardness, energy dispersive spectroscopy analysis and X-ray diffraction measurements were also performed to evaluate the characteristics of aged AA2124/SiC/25p composite. The results show that the hardness values of as-received composite were considerably improved up to two third by the subsequent aging. The hardness increasing was attributed to the presence of CuAl 2 , Al 4 SiC 4 and precipitation phases in aged AA2124/SiC/25p composite.